2017
DOI: 10.1088/1361-648x/aa602a
|View full text |Cite
|
Sign up to set email alerts
|

AlM2B2(M  =  Cr, Mn, Fe, Co, Ni): a group of nanolaminated materials

Abstract: Combining theory with experiments, we study the phase stability, elastic properties, electronic structure and hardness of layered ternary borides AlCr 2 B 2 , AlMn 2 B 2 , AlFe 2 B 2 , AlCo 2 B 2 , and AlNi 2 B 2 . We find that the first three borides of this series are stable phases, while AlCo 2 B 2 and AlNi 2 B 2 are metastable. We show that the elasticity increases in the boride series, and predict that AlCr 2 B 2 , AlMn 2 B 2 , and AlFe 2 B 2 are more brittle, while AlCo 2 B 2 and AlNi 2 B 2 are more duct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 48 publications
7
48
2
Order By: Relevance
“…AlFeMnB 2 has unit cell parameters similar to the other compounds, which is reasonable given the similar atomic radius for iron and manganese. There is a small difference between the unit cell parameters observed here (and previously by us [13,25]) and the parameters by Chai et al [11], which could be an indication of a possible homogeneity range of the AlM 2 B 2 phase. We have, however, prepared samples both in stoichiometric ratios between the elements (here) as well as with excess Al ( [13,25]) and these values are in close agreement with each other, suggesting that this is not the case.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…AlFeMnB 2 has unit cell parameters similar to the other compounds, which is reasonable given the similar atomic radius for iron and manganese. There is a small difference between the unit cell parameters observed here (and previously by us [13,25]) and the parameters by Chai et al [11], which could be an indication of a possible homogeneity range of the AlM 2 B 2 phase. We have, however, prepared samples both in stoichiometric ratios between the elements (here) as well as with excess Al ( [13,25]) and these values are in close agreement with each other, suggesting that this is not the case.…”
Section: Resultscontrasting
confidence: 57%
“…Whether the differences in hardness are an effect of the substitutions or coming from precipitations of secondary phases is not easily judged. Nevertheless, the values are significantly lower than normally found for metal borides [26], which can be attributed to the nanolaminated structure of these phases with weak bonds between the (M 2 B 2 ) and Al layers [24,25]. In figure 3 micrographs for the AlFeMnB 2 sample is shown, where indents with a diamond tip were made.…”
Section: Resultsmentioning
confidence: 93%
“…It is reasonable to assume that the Cr–Al–B MAB phases would exhibit high oxidation resistance. Although some ground‐state properties including crystal structure, chemical bonding, hardness, and elastic properties were investigated in the previous work, no systematic study of these compounds has been reported. Density functional theory (DFT) is an efficient method to be used in ab initio electronic structure calculations of periodic systems .…”
Section: Introductionmentioning
confidence: 99%
“…It effectively solved the traditional shortcomings of experiment, namely the high cost, low efficiency and long research and development time frames. In the field of MAB phases, significant theoretical investigations using DFT have been conducted, with many important problems solved. For instance, it has been revealed that the high elastic stiffness originates from the strong covalent B–B and M–B bonds, while the relatively weak Al1–Al2 bond contributes to the high fracture toughness and damage tolerance …”
Section: Introductionmentioning
confidence: 99%
“…Combining theory with experiments, Kádas et al studied the phase stability in T 2 AlB 2 with T = Cr, Mn, Fe, Co, and Ni. They found that although compounds are metastable with T = Co and Ni, Fe 2−x Co x AlB 2 , Fe 2−x Ni x AlB 2 , or even (Fe 2−x−y Co x Ni y )AlB 2 could be stable [8]. However, the magnetic properties of those alloys or even their parent compounds are not well understood.…”
Section: Introductionmentioning
confidence: 99%